Collars and Renegotiation in Mergers and Acquisitions - OFFICER, MICAH S. (Journal of Finance, 2004)
ABSTRACT I examine the motivation for, and effect of, including a collar in a merger agreement. The most important cross‐sectional determinants of the bid structure (cash vs. stock, and whether to include a collar) are the market‐related stock return standard deviations for the bidder and target. This evidence supports the hypothesis that the method of payment is dependent on the sensitivities of the bidder and target to market‐related risk because either has the incentive to demand renegotiation of the merger terms if the value of the bidder's offer changes materially relative to the value of the target during the bid period.